Cooperative binding of two E2F molecules to an Ela-responsive promoter is triggered by the adenovirus Ela, but not by a cellular Ela-like activity. - Jansen-Durr, P (1989)
The binding of the cellular E2F transcription factor to the central EIa-responsive element of the adenovirus EIIa early promoter (EIIaE) was compared in extracts of HeLa cells which had been infected with either wild-type adenovirus or the EIa-deficient mutant dl312. No quantitative differences in the E2F-binding activity were detected as a function of EIa gene expression. However, complexes formed by the E2F factor in the presence of EIa were qualitatively different from those formed on the same sequence element in the absence of EIa. Specifically, the formation of complexes containing two E2F molecules is favoured by EIa, probably through the induction of protein-protein interactions. Protein binding to EIIaE promoter in extracts from non-infected F9 embryonal carcinoma cells, prepared before and after in vitro differentiation of these cells was also analysed. The higher expression of EIIaE in undifferentiated cells, which was originally attributed to a cellular EIa-like function, may be correlated with the increased binding activity of a murine E2F-like protein which does not, however, result in the simultaneous occupation of both E2F sites on the EIIaE promoter, suggesting that the viral EIa and the presumptive cellular EIa-like functions trans-activate the EIIaE promoter through different pathways.